2016
DOI: 10.1371/journal.pone.0157030
|View full text |Cite
|
Sign up to set email alerts
|

Odor Impression Prediction from Mass Spectra

Abstract: The sense of smell arises from the perception of odors from chemicals. However, the relationship between the impression of odor and the numerous physicochemical parameters has yet to be understood owing to its complexity. As such, there is no established general method for predicting the impression of odor of a chemical only from its physicochemical properties. In this study, we designed a novel predictive model based on an artificial neural network with a deep structure for predicting odor impression utilizin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 22 publications
(18 reference statements)
0
20
1
Order By: Relevance
“…But even though the implication is that odor perception should be highly subjective, studies have shown that genetic variability in odorant receptors (ORs) contributes to odor perception. Equally, machine learning has accurately predicted perceptual descriptors of odorants from chemical features, suggesting that physicochemical properties influence perception ( Debnath et al., 2019 ; Gutiérrez et al., 2018 ; Keller et al., 2017 ; Khan et al., 2007 ; Licon et al., 2019 ; Nozaki and Nakamoto, 2016 ; Sanchez-Lengeling et al., 2019 ). Moreover, modeling human odor perception using a large semantic similarity space has shown that accurate predictions of perceptual ratings are possible even when training and prediction are done on completely different study samples.…”
Section: Introductionmentioning
confidence: 99%
“…But even though the implication is that odor perception should be highly subjective, studies have shown that genetic variability in odorant receptors (ORs) contributes to odor perception. Equally, machine learning has accurately predicted perceptual descriptors of odorants from chemical features, suggesting that physicochemical properties influence perception ( Debnath et al., 2019 ; Gutiérrez et al., 2018 ; Keller et al., 2017 ; Khan et al., 2007 ; Licon et al., 2019 ; Nozaki and Nakamoto, 2016 ; Sanchez-Lengeling et al., 2019 ). Moreover, modeling human odor perception using a large semantic similarity space has shown that accurate predictions of perceptual ratings are possible even when training and prediction are done on completely different study samples.…”
Section: Introductionmentioning
confidence: 99%
“…We previously proposed a predictive model of odor impression using a nine-layer neural network [ 7 ]. In the predictive model, which uses the results of Dravnieks’ evaluation test, 146 different odor characteristics were predicted with a correlation coefficient of 0.76 on a validation set.…”
Section: Introductionmentioning
confidence: 99%
“…nonlinear high dimensional space of mass spectra [9] into its bottleneck latent space. Then, these reduced feature vectors of mass spectra are used as an input to neural network to predict the odor descriptor groups.…”
Section: Plos Onementioning
confidence: 99%